A gap between the intention of the Swedish law and interactions between nurses and children of patients in the field of palliative oncology – The perspective of nurses. (June 2016) - Karidar, Hakima; Åkesson, Helene; Glasdam, Stinne
Abstract: Purpose: Children who have a parent with incurable cancer are in a vulnerable situation and the Swedish law tries to protect them. This article aims to explore the interactions between nurses and children of patients with incurable cancer from the nurses' perspective. Method: Semi-structured interviews with nine nurses in palliative oncology in Southern Sweden. Latent content analysis was carried out, inspired by Lundmann and Graneheim. Results: Parents are gatekeepers to the children's involvement and meetings with the healthcare professionals. Therefore the nurses were dependent on the parents for contact with their children. Additionally, nurses were subject to the structural frame of their working environment in terms of time, economy, resources and the medical logic ruling the priorities for nursing during their daily working day. The opportunities to pay attention to the children of patients were limited, despite good intentions, willingness and a favourable legal framework. Teenagers were regarded as a challenge, and per se they challenged the nurses' opportunities to gain control of the meetings and situations around the families. Conclusions: Often nurses did not see and acknowledge the children of the palliative patient. They knew that the children were there and that it was important that they were there, but they challenged the order in the working environment in relation to time-allocated tasks and working flow. In the working environment patients were prioritised over relatives. From the perspective of nurses, there is a gap between the intentions of the Swedish law and the interactions between nurses and children. Highlights: Parents are gatekeepers to the children's involvement and meetings with the healthcare professionals. Nurses are subject to the structural frame of the system which limited their possibilities for interactions with children. The opportunities to pay attention to patients' children were limited, despite good intentions, willingness and a favourable law.